Cultivating Islamic Virtue and Leadership: Strategic Management of Mosque-Based Youth Education as a Habituation Framework - Awaludin Sidik; Fitriyani Kosasih (Jurnal Iman dan Spiritualitas, 2026)
As the nation's next generation, adolescents are highly vulnerable to the negative impacts of technological developments and globalization. One of the most obvious impacts is the shift in Islamic values in their daily lives. Furthermore, instilling leadership values is urgent, as adaptive leadership habits relevant to global dynamics are necessary from adolescence onward. The Mosque Youth Association (IRMA) is one such organization with the potential to be a strategic solution in fostering Islamic values while fostering leadership character. This study aims to describe the application of management functions, including planning, organizing, implementing, and supervising, to support the instillation of Islamic values and leadership through IRMA activities. The study employed a descriptive qualitative approach, with data triangulation techniques through observation, interviews, and documentation to obtain a comprehensive picture of the phenomenon under study. The results indicate that management functions have been implemented effectively. In the planning stage, the program is systematically structured through goal setting, member recruitment mechanisms, and annual program development. The organizing stage is evident in the structured division of tasks and the provision of resources to support activities. Program implementation proceeded according to schedule with active member participation, while monitoring was conducted through periodic evaluation and reporting of activity results. This study concluded that sound management enabled IRMA's activities to be effective and sustainable in fostering Islamic values and youth leadership.